Response of plant density on growth, yield and quality of Pomegranate cv. Ganesh (Indian Journal of Arid Horticulture, 2013)
An experiment on response of planting density on growth, yield and quality of pomegranate cv. Ganesh was  conducted during 2001 to 2004 in the Experimental field of Central Horticultural Experiment Station, Vejalpur,  Panchmahals, Gujarat under JVG-NATP-HFNS project. Pomegranate variety cv. Ganesh was planted at four different  spacing levels i.e. 5m x 5m (T ), 5m x 3m (T ), 4m x 2m (T ) and 2.5m x 2.5m (T ) having density of 400, 666, 1250 and 1600 1 2 3 4 plants per ha, respectively in randomized block design with five replications purely under rainfed conditions of hot semi arid ecosystem. Maximum plant height was recorded with planting density 2.5 m x 2.5m, while plant spread and stem girth  rd was observed with 5m x 5m spacing during 3 year. With regard to spacing, yield (3680 kg) per ha was recorded the  maximum with plant density 2.5m x 2.5m, whereas size (6.50 cm x 6.90cm) of the fruit and quality characters were  recorded the maximum in the planting density 5m x 5m under rainfed conditions of semi-arid ecosystem of western India.
Keywords: Pomegranate; density; yield; quality